2013
DOI: 10.3839/jabc.2013.040
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Sargauum fulvellum Ethanolic Extract on LPS-Induced Inflammatory Reaction in RAW 264.7 Mouse Macrophages

Abstract: Recently, algae has been considered as a potential antiinflammatory source due to its distinctive habitat environment exposing to light and high oxygen concentration. In present study, anti-inflammatory effect of brown alga, Sargassum fullvellum ethanol extract (SFEE), was examined. SFEE inhibited not only the production of nitric oxide and pro-inflammatory cytokines (IL-6, IL-1β, TNF-α) but also the expression of inducible nitric oxide synthase and cyclooxygenase 2 in LPS-induced RAW 264.7 cells without affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…These facts indicated that the relatively lipophilic compounds tended to be responsible for the anti-inflammatory activity. This was supported by several other studies showing a similar tendency that a relatively lipophylic extract or fraction has a promising anti-inflammatory effect [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33].…”
Section: Sargassum Species Are a Source Of Anti-inflammatory Agentssupporting
confidence: 75%
“…These facts indicated that the relatively lipophilic compounds tended to be responsible for the anti-inflammatory activity. This was supported by several other studies showing a similar tendency that a relatively lipophylic extract or fraction has a promising anti-inflammatory effect [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33].…”
Section: Sargassum Species Are a Source Of Anti-inflammatory Agentssupporting
confidence: 75%
“…The reason for the decrease in NO secretion could be the monosaccharide formation by the breakdown of alginic acid polysaccharides (Figure 1). These results showed that the NO inhibition activity of SFEE using crude enzyme from S. oneidensis PKA 1008 was higher than treatment with the S. fulvellum ethanolic extract at 100 µg/mL (Kim et al, 2013). In addition, in a study investigating the inhibitory effect of U. pinnatifida root (UPT) enzymatic extract on NO production in LPS-induced RAW 264.7 cells, the secretion of NO by LPS stimulation was significantly inhibited by UPT enzymatic extract treatment (Xu et al, 2020).…”
Section: Effect On Lps-induced Nitric Oxidementioning
confidence: 93%
“…SFEE also suppressed the expression of NF- κ B, suggesting that SFEE could affect the expression of inflammation-related cytokines and proteins through the regulation of NF- κ B. Furthermore, the formation of ear edema was 40% lower in mice treated with the highest dose (250 mg/kg) of SFEE than that in the control mice [ 57 ].…”
Section: Biological Activities Of S Fulvellummentioning
confidence: 99%